Mining An Open Pit Over And Through Old Sub-Level Caving Operations At Kwaggashoek East Open Pit, Thabazimbi Iron Ore Mine - C J. de Beer (The Southern African Institute of Mining and Metallurgy, 2006)
The Kwaggashoek East pit is one of the four production areas of Thabazimbi Iron Ore Mine. The Kwaggashoek East Open pit mines through the abandoned sublevel caving operations of the Kwaggashoek East underground workings. A risk assessment indicated that the primary risk is the occurrence of surface subsidence. Based on local knowledge, a hypothesis, that most of the cavities were filled with broken rock as a result of roof collapse and bulking of failed material was formulated. To test the hypothesis a number of geophysical methods as well as probe drilling was utilized. The results of the resistivity, gravity and ground penetrating radar surveys were inconclusive in determining the position of voids. Either there were no voids present or the resolution of the surveys was not high enough to pick it up. It is accepted that only small voids remained, and that the supported roof hypothesis is valid. As a precautionary measure all the production blast holes within the caving area were over-drilled by forty percent. This would collapse the roof of any small voids or tunnels immediately below the block. This operation proved to be successful as two of the three underground levels have been mined out with no subsidence occurring in the pit floor.